Secondary eclipses of WASP-18b – near-infrared observations with the Anglo-Australian Telescope, the Magellan Clay Telescope and the LCOGT network. Issue 4 (13th December 2018) - Kedziora-Chudczer, L; Zhou, G; Bailey, J; Bayliss, D D R; Tinney, C G; Osip, D; Colón, K D; Shporer, A; Dragomir, D
ABSTRACT: We present new eclipse observations for one of the hottest 'hot Jupiters', WASP-18b, for which previously published data from HST WFC3 and Spitzer have led to radically conflicting conclusions about the composition of this planet's atmosphere. We measure eclipse depths of $0.15± 0.02{{\ \rm per\ cent}}$ at Ks and $0.07± 0.01{{\ \rm per\ cent}}$ at z ′ bands. Using the vstar line-by-line radiative transfer code and both these new observations with previously published data, we derive a new model of the planetary atmosphere. We have varied both the metallicity and C/O ratio in our modelling, and find no need for the extreme metallicity suggested by Sheppard et al. Our best-fitting models slightly underestimate the emission at z ′ band and overestimate the observed flux at Ks band. To explain these discrepancies, we examine the impact on the planetary emission spectrum of the presence of several types of hazes which could form on the night side of the planet. Our Ks- band eclipse flux measurement is lower than expected from clear atmosphere models and this could be explained by haze particles larger than 0.2 μm with the optical properties of Al2 O3, CaTiO3 or MgSiO3 . We find that z ′-band measurements are important for understanding the contribution of photochemical hazes with particles smaller than 0.1 μm at the top of the atmosphere.